2022
DOI: 10.1371/journal.pone.0272552
|View full text |Cite
|
Sign up to set email alerts
|

A sense of belonging: The role of higher education in retaining quality STEM teachers

Abstract: There is an alarming shortage of qualified STEM teachers in American PK-12 schools. The COVID-19 pandemic may exacerbate this crisis and consequently affect who participates in future STEM innovation. At three points during the pandemic, we surveyed early career teachers who were supported by the National Science Foundation as they began teaching in high-needs school districts. Teachers who felt connected to their professional and academic communities reported intentions to remain in the profession, while thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…For example, Noyce programs often provide regular professional development support during student teaching and the first few years of teaching to create a sense of community (Polizzi et al, 2021). In another study, we found that teachers who felt they belonged to and were valued by their alma mater during the pandemic, indicated plans on remaining in the teaching profession (Balgopal et al, 2022). By feeling connected to and supported by professors and institutions, teachers are reminded that they have these resources available to them, allowing them to leverage capitals accrued during their education and content studies (Fuller & Pendola, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…For example, Noyce programs often provide regular professional development support during student teaching and the first few years of teaching to create a sense of community (Polizzi et al, 2021). In another study, we found that teachers who felt they belonged to and were valued by their alma mater during the pandemic, indicated plans on remaining in the teaching profession (Balgopal et al, 2022). By feeling connected to and supported by professors and institutions, teachers are reminded that they have these resources available to them, allowing them to leverage capitals accrued during their education and content studies (Fuller & Pendola, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Such variability means that novice teachers likely fall on a continuum of high and low resilience that may be influenced by their sense of agency or control over their professional decisions. These factors, in turn, may impact their decisions to remain in or leave teaching (Balgopal et al, 2022). Building on the foundations of teacher agency theory (Biesta & Tedder, 2007) and capital theory (Liou & Canrinus, 2020), this study aims to explore the intertwined roles of agency and capital in the context of science teachers during the pandemic.…”
Section: Capital Theorymentioning
confidence: 99%
“…People's capacity to manage their environments and how they function within them is affected by their perception of the challenges they face and the capitals available to help address these challenges (Balgopal, 2020; Balgopal et al, 2022; Wright et al, 2023). Therefore, we assume that science teachers who have achieved agency, demonstrating a “mindset and disposition to respond to changing conditions” of schools during the pandemic (Ehren et al, 2021, p. 62), are likely to have done so by drawing on a range of capitals, both intrinsic (e.g., psychological) and extrinsic (e.g., professional learning community).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations